Role of HR in Promoting Sustainability and Corporate Social Responsibility - Mathew , Dr. Jisha Mary; Fasina, M.; Biju , P.J.; Hamsa , E. (International Journal of Accounting and Economics Studies, 2025)
This article focuses on human resources (HR) and its possibilities to improve environmental sustainability and CSR within companies. HR departments are in a solid position to support sustainable practices and a CSR culture as companies give ESG (environmental, social, and governance) problems top priority more and more importance. The study looks at HR policies that support employee involvement, training, leadership development, and ethical recruiting so that sustainability and CSR may be included in business objectives. Human resources' impact on corporate strategies prioritizing community involvement, employee well-being, and environmental sustainability is also examined. The study uses qualitative and quantitative methods to investigate the effects of HR-driven initiatives on organizations' performance, reputation, and long-term viability. The findings show that HR is essential for advancing CSR objectives and creating a sustainable workforce. The report concludes with suggestions on how human resource managers might better contribute to sustainable business practices and responsible corporate citizenship.